Global Warming and Climate Change Effect: Understanding the Interplay between Environmental Impact and Geopolitical Conflict - Anasta, Sri Wilda; Kusyairi, Rifyal Zaihifni Fadli; Aditya, Muhamad Luthfi; Hanif, Muhammad Hudan (Candidate: Jurnal Sains Politik, 2023)
Climate change emerges as a critical catalyst for international conflicts, intensifying geopolitical tensions and socio-economic instability through environmental degradation. This analysis reveals how escalating greenhouse gases profoundly impact global ecosystems, spotlighting the strategic roles and geopolitical complexities involving major nations, especially China’s influence. Employing qualitative methods, the study scrutinizes the effectiveness of international agreements like the UNFCCC, Kyoto Protocol, and Paris Agreement. It exposes gaps in understanding localized impacts and effective mitigation strategies, advocating for an integrated approach that melds environmental science with socio-economic considerations. The research underscores the urgent need to merge environmental sustainability with strategic geopolitical and economic policies, aiming to effectively address the multifaceted challenges of climate change and ensure global stability.